Measuring Gender Equality - Posadas, Josefina; Paci, Pierella; Sajaia, Zurab; Lokshin, Michael (Washington, DC: World Bank, 2017)
Gender equality is a core development objective in its own right and also smart development policy and business practice. No society can develop sustainably without giving men and women equal power to shape their own lives and contribute to their families, communities, and countries. And yet, critical gender gaps continue to exist in all countries and across multiple dimensions.